Coupling effect of condensing temperature and residence time on bio-oil component enrichment during the condensation of biomass pyrolysis vapors. (15th August 2020) - Wang, Chu; Luo, Zejun; Li, Shiying; Zhu, Xifeng
Highlights: Bio-oil preparation experiments were conducted at different condensing conditions. Bio-oil composition were analyzed with condensing temperature and residence time. Optimal condensing conditions were given for enriching high value-added compounds. Equivalent relationship was provided for preventing high condensing temperatures. Abstract: Walnut shell pyrolysis condensation experiments were conducted at different condensing temperatures (323 K, 333 K, 343 K, 353 K and 363 K) and residence times (2.3 s, 2.6 s, 3.0 s, 3.5 s and 4.1 s) to analyze the coupling effect of these variables on the separation and enrichment of bio-oil components. The content of guaiacol and its derivatives increased by 150% at the expense of the considerable reductions in condensing efficiency and bio-oil moisture when the condensing effect of pyrolysis vapors was substantially inhibited. With decreasing residence time, the contents of acetic acid and furfural increased by 20% at 333 K but decreased by 50% at 363 K. The equivalent relationships between condensing temperature and residence time were established to separate target components and prevent high condensing temperatures. Considering condensing efficiency and component distribution, the efficient condition for dewatering was 343 K condensing temperature and 2.6 s residence time. The optimal conditions for acetic acid enrichment and separation were 323 K and 3.0 s and 363 K and 4.1 s, respectively. The condensing condition of 363 K and 3.0 s could be applied to the concentration of guaiacol and its derivatives.